HPLC Estimation of Withaferin-A and Boswellic Acid in Formulated Gels. - Rajendra, C E (International Journal of Pharmaceutical & Biological Archive, 2010)
Withania somnifera and Boswelia serrata are important drugs of many ayurvedic preparations. The interactions of the ingredients in the process of formulations are unimaginable. Hence, the attempt made in order to assess the concentration of Boswellic acid and Withaferin A in the formulation. 2% W/W each of Methanolic Extracts of Withania somnifera and Boswellia serrata were prepared, incorporated in gel formulations using different polymers and estimated the content of withaferin A & Boswellic Acid in the formulations using HPLC method. The result shown 95-105% of expected Withaferin A and 96-104% of expected Boswellic acid in formulations